Small field output factors: Comparison of measurements with various detectors and effects of detector orientation with primary jaw setting. (February 2016) - Godson, Henry Finlay; Ravikumar, M.; Ganesh, K.M.; Sathiyan, S.; Ponmalar, Y. Retna
Abstract: Accurate dosimetry in small photon fields used in modern radiotherapy is a challenging task due to electronic disequilibrium, steep dose gradients, source occlusion and size of the sensitive volume of the detector. These challenging effects and the lack of metrological dosimetric reference instigated an investigation on the acquisition of output factor with various detectors in parallel and perpendicular orientations. Small field output factor measurements of tertiary collimators such as BrainLab circular cones, BrainLab mMLC and Millennium MLC were carried out in this study. The data acquired show the differences between output factor results with different detectors for all collimating systems. Good agreement in output values was observed in field sizes greater than ∼2 × 2 cm 2 for all detectors and all tertiary collimators. For smaller fields when compared to electron field diode (EFD), 0.125 cm 3 ion chamber underestimates the output by up to −11.1% and −20.4% and pinpoint ion chamber underestimates the output by up to −1.5% and −6.1% in their parallel and perpendicular orientation, respectively. In contrast, PTW SRS diode and photon field diode (PFD) overestimate the output factor by up to 2.5% and 6.9% respectively in its parallel orientation. The investigated data for the effect of jaw position (0.25 × 0.25 cm 2, 0.5 × 0.5 cm 2 and 1 × 1 cm 2 ) away from the field edge generated by different tertiary collimating systems inferred that the opening of X–Y jaw highly influences the small field output factors. The orientation of the detectors and the position of the jaws could influence the output factors considerably in small fields. Highlights: Output factors vary significantly with various detectors for the smallest field of all collimating systems. Small field output factors depend on the configuration of secondary as well as tertiary collimating systems. The detector orientation and the position of jaws influence the output factors considerably in small fields.